RELATIONSHIP OF VENOUS RECANALIZATION WITH QUALITY OF LIFE AND SEVERITY OF THE DISEASE IN PATIENTS WITH VENOUS ULCER SUBMITTED TO POLIDOCANOL FOAM SCLEROTHERAPY - Ballaminut da Silveira, Lara (2017)
Introduction: Venous ulcer is the most advanced stage of chronic venous disease. Polidocanol foam sclerotherapy corresponds to a minimally invasive treatment, reproducible in cases of vessel recanalization. Objective: To correlate the severity of venous disease, quality of life and recanalization rates in patients with venous ulcers treated with polidocanol foam sclerotherapy. Methods: Forty patients with venous ulcers submitted to ultrasound-guided polidocanol foam sclerotherapy were evaluated. The patients were divided into four groups according to the post-procedure period (Group 6, Group 12, Group 24 and Group 36). Quality of life, severity of disease and vein recanalization were analyzed in all patients using the generic questionnaire SF-36, the Clinical Severity Scale of the Venous Symptoms and Doppler ultrasonography, respectively. Results: There was no statistically significant relationship between vein recanalization with the eight SF-36 domains or with the higher scores of the Clinical Severity Scale of Venous Symptoms in any of the groups studied. When comparing the domains of SF-36 between groups there was statistically significant difference in the domain limitations by emotional aspects (p<0.05). Conclusion: Vein recanalization does not affects negatively the quality of life and the severity of disease in patients submitted to polidocanol foam sclerotherapy.